Building Religious Product Advantage to Increase Marketing Performance of Micro, Small and Medium Halal Industry in Central Java - Indonesia - Hanfan, Ahmad; Hapsari, Ira Maya; Setiawan, Ahmad Ikhwan; Nupus, Hayati (JDM (Jurnal Dinamika Manajemen), 2023)
This research examined and explored the role of religious product advantage to improve marketing performance. Religious product advantage represented the company's advantage to placing products in the minds of consumers by using the uniqueness of syariah products, unique consequence products and irreplaceable experiential products. This advantage indicated that the products produced by the company were more distinctive and unique than competitors' products. This research is based on a survey of 155 halal industry MSMEs respondents in Brebes, Central Java. The proposed hypotheses were tested using Structural Equation Model using the AMOS program. The results found that religious product advantage could increase sales volume, number of buyers, growth in profits and sales. The halal industry MSMEs have the specifics and uniqueness of syariah products, they did not require product configuration capability that were always changing. Product configuration capability has no effect on religious product advantage. This research was expected to provided a contribution to both theoretical and practical knowledge of strategic management. Business players had focussed on developing company advantages to address the constantly changing business environment.